Molecular mimicry-driven autoimmunity in chronic rhinosinusitis with nasal polyps - Asamori, Tomoaki; Katoh, Hiroto; Takata, Mikiya; Komura, Daisuke; Kakiuchi, Miwako; Hashimoto, Itaru; Sakurai, Madoka; Yamamoto, Asami; Tsutsumi, Takeshi; Asakage, Takahiro; Ota, Yasushi; Ishikawa, Shumpei (Journal of allergy and clinical immunology, 2025)
[Display omitted] The pathogenesis of chronic rhinosinusitis with nasal polyps (CRSwNP) remains a subject of discussion. Although both microbial infection and autoimmunity have been proposed as potential contributors to CRSwNP pathobiology, their respective roles and intricate interactions in disease progression remain unclear owing to the limited knowledge regarding dysregulated humoral immunity in CRSwNP. To deepen understanding of CRSwNP, we sought to identify the precise humoral antigens targeted by dominant B-cell clones within the disease environments. Immunoglobulin repertoire sequencing was performed to identify dominant B-cell clones in CRSwNP tissues. These immunoglobulin clones were reconstructed as antibodies, which were then used in immunoprecipitation and antigen array experiments for hypothesis-free global antigen profiling of autogenous and exogenous antigens. From analysis of 13 patients with CRSwNP, 31 antibodies were reconstructed from dominant B-cell clones identified in 9 patients. Seven novel protein autoantigens were identified, 5 of which were nucleic acid–binding proteins, and all were associated with autoimmune diseases. Additionally, 9 microbial antigens, including various viruses, bacteria, and fungi, were discovered. Notably, 2 antibodies demonstrated dual reactivity, simultaneously recognizing both microbial and human proteins. For example, 1 antibody targeted cytomegalovirus, Clostridium tetani, and human PLEC, whereas another recognized Aspergillus niger and human DLAT, through molecular mimicry of shared amino acid homologies. Our data indicate the possibility that the pathobiology of CRSwNP involves autoreactive humoral immunity, with a subset of cases potentially exhibiting molecular mimicry–driven autoimmune features triggered by microbial infections. Nevertheless, this hypothesis requires further investigation.